PENDAMPINGAN MENINGKATKAN KESADARAN DAN PERILAKU BAIK DALAM MENGGUNAKAN GADGET PADA ANAK NELAYAN MELALUI VIDEO EDUKATIF - Hidayah, Linta Wafdan; Mulyadi, Mulyadi; Tamam, Badrut (Universitas Al-Amien Prenduan, 2025)
Not only adults, but also school-age children are often greatly impacted by the rapid developments in this technological era. Smartphones, or what we better know as gadgets, seem to be a mandatory item that parents must provide for their children so they don't miss out on fast information. The use of gadgets does have many positive impacts for school-age children, for example increasing knowledge and experience that they have never had before, but sometimes the negative impacts outweigh the positive ones. In fact, many experience negative impacts and addiction. The impact of gadget addiction greatly affects the emotions and behavior of children who are addicted to gadgets. Therefore, the author and the community service team provided education to fishermen's children about the dangers of gadgets through educational videos. In this case, the community service team used two videos in the community service implementation. The first video from Pondok Kreativ entitled